Shopee SPayLater Syari’ah Business Management in the Perspective of the Qur'an - Churin In; Siti Rifqiyatul M; Sariah Nailla Q; Hidayatul Maulidia; Ayunda Hanum F (Jurnal Al-fatih Global Mulia, 2024)
As time goes by and technology advances, purchases can not only be made offline but can also be made online. Currently, many shops are starting to join and adapt to the digital world because of the increasingly diverse consumer behavior in making purchases. Shops are currently collaborating with the marketplace world that helps the online buying and selling process. One of the marketplaces that is widely visited by Indonesian consumers is Shopee. Shopee provides a variety of community needs in various choices. The payment system on Shopee also has many choices, including the COD system (pay on the spot), Shopeepay, via Bank and there is also a shop now pay later or later week system known as the SPayLater system. This study analyzes Sharia Business Management on the SPayLater service on the Shopee platform through the perspective of the Qur'an, with a focus on the application of Islamic principles in financial practices. This service that allows users to shop with deferred payments poses challenges related to compliance with the prohibition of usury and the principle of fairness in transactions. Through a qualitative approach, this study explores how Shopee seeks to integrate Sharia values, such as transparency and responsibility, into its operations. The research findings show that although SPayLater offers easy access for consumers, there is a risk of public misunderstanding regarding Sharia compliance in this system. This research is expected to provide insights for the development of Sharia financial products and strengthen the understanding of the application of the teachings of the Qur'an in modern business.